TIPE 21 - Pitri Ermawati (Rekam: Jurnal Fotografi, Televisi, Animasi)
“Type 21” is a metaphor of tomb, a place mostly two by one square in size.Everybody will die, their dead bodies are placed in the tomb then. Most people are scared of tomb for some reasons. But in my opinion, the tomb is such interesting subject to be photograped. As trying to apply De Bono’s lateral thinking method, I got close to the tomb and explore it photographically. Then here it is a project of art photography with tomb as subject. The photographs printed in black and white to represent the life after death that’s both enigmatic or mysterious for human who is still living in this world right now. The photographs were created by outdoors hunting in several cemetery. There, I shot tombstones and the other things around these. Taking picture by mostly close up technique makes the detail of the subjects to appear vivid and real. Generally, the subjects are visualized in simbolism. Although there are vagueness, their identities still can be read. By specific technique of taking picture, the subjects in the frame look much different than the real subjects in the fields when it were photographed.I hope this project will enrich the field of art photography with tomb as thesubject. I hope it can also be a trigger to other photographers in creating such project base on the unusual subjects. All religion order their people to stay out of sin. Thus, hopefully my project can be an alert for people in remembering death, so they are afraid to be sinful and to heart each others. Because after this life there will be the life after death that will ask for people’s responsibility. Thus, at least people can eliminate hurting each others.